Estudio de factibilidad para la creación de una empresa productora de pesticidas a base de barbasco en el cantón Palora, provincia de Morona Santiago y su comercialización en la provincia de Pastaza - Palomeque Vásquez, Inés Beatriz (2015)
For this thesis General has set targets to determine the feasibility of creating a production company based pesticides barbasco in the canton Palora and marketing in the province of Pastaza, which has considered the application of different methods and Techniques that research permits, as the Inductive Method it gave a guideline to determine the general conclusions of the project, the Deductive Method based on this sample size, with general and real data of the population was determined local potential demand, real, effective and unmet demand, the synthetic analytical method which allowed to apply management science and through which the generalizing laws of pesticide production company based barbasco were determined, the statistical method in change allowed measuring the results of the surveys, and the highest percentage of which is determined the problem allowed to determine the feasibility of creating a production and marketing company based pesticide barbasco. In the market study in the province of Pastaza, with a sample of 393 families; Weighted surveys have been analyzed and the results have been inferred then perform market analysis, determining the potential demand of 23,995 families, 12,477 families Demand Real, Effective Demand 11,230 families and 134,756 liters of pesticide, The Offer of 12,002 liters of pesticides and unmet demand for 122,754 liters of pesticides, which allowed us to determine that the project can and should be run by the results obtained in the analysis of demand, supply and marketing levels for this product. The unmet demand reflects the potential that exists in the province cited for this product market with the following results: For the first year of life of the project is unmet demand: 122,754 liters of pesticides, the installed capacity of the project determines that the company will be able to produce 65,664 liters of pesticides and whose capacity utilization will be 52,531 liters of pesticides, which produce 80% of capacity utilization for the first year which corresponds to 52,531 liters of pesticides also determined the location thereof to be located in the city of Palora, in Olmedo and J. Reinoso streets. The production process requires the use of suitable equipment, which will guarantee for a quality product at reasonable prices. Then the project engineering process diagrams determining the characteristics of operation and management, technical requirements such as equipment, facilities, furniture and fixtures developed. Also an administrative study determined as a Limited Liability Company, and the functional organizational structure hierarchical levels both Legislative, Executive, Consultant Level Support Assistant, Operational Level Level as well as operating manuals, charts was performed; which served as a guideline for implementing a good organization, since there will be the following personnel: Manager, a Secretariat a Concierge-Guardian, one Accountant who will be part of the administrative staff and operational staff distributed as follows: a Head production, a Head of Sales two Workers, and a seller. The project reaches an investment of $ 45,668.14 and will be financed with contributions from partners the 56,21% of the total investment corresponding to $ 25,668.14 and a loan that will keep the project with the Banco de Guayaquil constitute the 43.79% which corresponds to $ 20,000 a 10 year period to 15.00% annual interest. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 132,401.84, which indicates that the project or investment is suitable. For this project IRR is 71,90%, this being satisfactory value for the project, the time it would take to recover the original investment would be 1 year, 4 months and 18 days, for this project, the sensitivity values are less than one, so do not affect the project changes in costs and increased revenues decreased 25.4% and 18.8%, respectively, ie the project is not sensitive to these changes. Among the most significant findings and recommendations have, that the market study developed in the province of Pastaza, determines that the project can and should be run by the results obtained in the analysis of supply and demand. It has been shown that there is considerable unmet demand for the product to be developed, which with the implementation of our company, at 80% capacity, will be covered in 51.63%. At this product to be known in the market, while having a strong competition requires a permanent campaign is implemented using existing facilities as noted by our marketing proposal